Gender-Affirming Treatments to Children with Gender Dysphoria - Taqwa, Muhamad Dzadit; Yuubina, Venitta; Manurung, Stephen Joy Herald (Journal of Southeast Asian Human Rights, 2024)
Gender dysphoria occurs not only in adults but also in underage children. Their inner conviction that their gender identity does not align with their physical body leads to a desire to alter their physical appearance through gender-affirming treatment(s) that affirm their gender identity. Examples include genitoplasty, puberty blockers, and cross-sex hormone therapies. Proponents argue that these desires should be accommodated because everyone, including children, has the right to determine what can be done to their own bodies. Moreover, some findings suggest that such treatments can have positive psychological benefits for these children. On the other hand, opponents question whether the consent given by children who desire such treatments is legitimate. Additionally, providing irreversible medical treatments solely to affirm gender identity can have physiological and psychological impacts. Thus, instead of affirming the desires of these children, medical physicians should focus on saving them from irreversible medical actions. This discourse is conducted by considering proportionally the constitutional rights of children, which need to be balanced with ensuring their knowledge and maturity in making decisions. Keywords: Children, Gender Dysphoria, Gender-affirming Treatments, Constitutional Rights